The effect of quality attributes in determination of price for plantation-grown Teak (Tectona grandis) logs in Sri Lanka - Jayawardhane, J.K.P.C.; Perera, P.K.P.; Lokupitiya, R.S.; Amarasekara, H.S.; Ruwanpathirana, N. (ANNALS OF FOREST RESEARCH, 2015)
Attached

Teak (Tectona grandis) is one of the highly demanded timber spe- | cies in Sri Lanka. When buying teak logs, customers assess their quality by p visual appraisal of surface characteristics such as visible defects. Hence, the p buyers’ preference for logs with desired attributes is reflected by the price s achieved in the market. In this study, we examined the influence of visually I observable quality attributes of plantation grown teak logs on their market | price. A set of 650 randomly selected teak logs were assessed for dimen- | sions, shape defects, surface defects and end-defects. Length of the log, p mid-circumference (under bark), diameter at top-end and butt-end, number I of knots per meter, average diameter of the knots, bend fraction, percentage I of heartwood, shape of the log, presence of buttress, position of the hollows, 1 presence of felling damages, splits and heart rot were recorded using standI " aid methods. Selling prices of logs were obtained from the records of log storing facilities. By using the multiple linear regressions, a price-quality model was developed to explain the impact of quality attributes on selling price. The regression model achieved a strong coefficient of determination (R!) of 0.87. Accordingly, the length, mid-circumference, number of knots per meter, bend fraction, hollow position, presence of buttresses and presence of heart rot were found to have a significant influence on the price. The relative price reduction due to presence of a specific log defect was further examined using the derived price-quality model. The presence of high number of knots had the highest detrimental impact on price, followed by the higher bend fraction, presence of hollows at top end and/or middle of the log, presence of heart rot and presence of buttresses respectively. These findings have implications in the improved management of teak plantations.
Keywords: wood quality attributes; timber defects; buyers’ preference; hedonic pricing; price-quality model